2021
DOI: 10.1111/epi.17038
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic nonepileptic seizures treated as epileptic seizures in the emergency department

Abstract: Objectives:We aimed to estimate the rate of psychogenic nonepileptic seizures (PNES) among patients presenting to an emergency department with presumed seizures. We also wanted to identify factors that can assist health care professionals in determining whether these events are likely to be epileptic or nonepileptic. Methods:We performed two retrospective audits on patients who were treated for seizures in the department of emergency medicine at the Princess Alexandra Hospital, Brisbane, Australia. Exploratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
17
1
Order By: Relevance
“…Consequently, previous postictal lactate measurements were higher than in our study, ranging from 3.0 to 6.9 mmol/L compared with 2.1 mmol/L. Prolonged PNES lactate levels were similar in our cohorts at 1.25–1.4 mmol/L compared with past studies where lactate was between 1.3 and 1.7 mmol/L with the upper end of the range representing pPNES 5,22,25 …”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Consequently, previous postictal lactate measurements were higher than in our study, ranging from 3.0 to 6.9 mmol/L compared with 2.1 mmol/L. Prolonged PNES lactate levels were similar in our cohorts at 1.25–1.4 mmol/L compared with past studies where lactate was between 1.3 and 1.7 mmol/L with the upper end of the range representing pPNES 5,22,25 …”
Section: Discussioncontrasting
confidence: 51%
“…Psychogenic nonepileptic seizures (PNES) are a common source of epilepsy misdiagnosis [1][2][3][4] and the rate of misdiagnosis may be higher in those with prolonged "status epilepticus-like" events. 5,6 Conversely, incorrectly diagnosing epileptic seizures as nonictal phenomena can also occur; one study in a neurological ICU setting, demonstrated a 15.6% rate of misdiagnosis of seizures as nonictal phenomena. 3 Misdiagnosis often results in inappropriate treatment which can have serious risks for patients.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis may be missed at acute presentation, when our cohort was identified, with some people instead diagnosed at a later stage, during hospital admission or at outpatient clinic. For example, other studies have shown that functional seizures are commonly misdiagnosed as epilepsy in acute settings [24,25]. This is a major limitation, as our approach to recording functional presentations relied on information provided by non-specialist clinicians, so it is likely than many patients presenting acutely with functional symptoms were not included in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty studies 15–34 reported the prevalence of injuries without specifying the type. Twenty‐two studies investigated tongue, cheek, or lip biting 4,17,19,21–23,31,33,35–48 . Eight studies reported other types of injuries, such as dental injuries, 35,36,48 fractures (e.g., leg, nose, pelvis), 35,36,44,48,49 bruises, 36,44 burns, 35,36,44,45,48 lacerations (e.g., face, scalp, limb), 35,36,42,44,48 and head injury 48,50 …”
Section: Resultsmentioning
confidence: 99%